Clinical and cyto-histopathological evaluation of skin lesions with special reference to bullous lesions - Sabir Fauziya; Aziz Mehar; Afroz Nishat; Amin S (Wolters Kluwer Medknow Publications, 2010)
Aim: Cytopathology of skin has been documented to be useful in the diagnosis of several skin lesions. This study aims to evaluate cytopathology as a quick non-invasive method for early diagnosis of bullous lesions, neoplastic and preneoplastic skin lesions and to correlate the clinical, cytological and histopathological findings of various skin lesions. Materials and Methods: Eighty five patients of skin lesions were included in the study. Skin scraping, Tzanck smears, slit smears and fine needle aspiration cytology (FNAC) were done to obtain material for cytological examination. Excisional biopsy, incisional biopsy and punch biopsy were done to obtain tissue for histopathological examination. The slides were stained with routine stains and special stains as and when required. Results: Of the 85 patients, 45 were males and 40 females. The most common non-neoplastic lesions observed were vesicobullous lesions which comprised of 41 cases followed by neoplastic lesions which consisted of 24 cases, of which six were benign and 18 malignant. Concordant results between cytology and histopathology was seen in majority (91.7%) of lesions studied. Conclusion: Cytology (scrape/imprint/slit smears and FNAC), performed skillfully and with perfection, leads to an early diagnosis in majority of the lesions, as the observed cytomorphological features of various skin lesions were fairly distinctive making cytology a fairly sensitive ′patient compliant′ technique for rapid diagnosis of skin lesions.